Pengembangan Bahan Ajar IPS Kontekstual Tema Wirausaha di Kelas 6 Sekolah Dasar - Sofia Agustin Adhaningrum (Jurnal Penelitian dan Pendidikan IPS, 2020)
The results of observations conducted on the students of Class VI SDN 2 Kalirejo on 7-9 December 2019, showed the lack of learning activities caused by the limited textbooks, the lack of material on textbooks related to student life and teacher-centered learning. So, based on needs analysis, adequate textbooks are needed in line with the number of students whose material is derived from the daily life of students and the application of relevant learning strategies is a must. Efforts made to overcome this is conducting research and development that aims to produce the contextual-based, valid, interesting, practical and effective textbooks of Social Science (IPS). The model used in this research and development was 4D model. The 4D model (Thiagarajan, S., Semmel, DS, & Semmel, MI: 1974)) consists of Define, Design, Develop and Disseminate. Teaching-learning process used contextual approach or Contextual Teaching and Learning (CTL). The data were analyzed qualitatively and quantitatively. The data was based on the assessment of material and linguists experts were considered valid. The results of product attractiveness test from the questionnaire given to students and teachers showed very interesting criteria. This material was very practical. This was based on the result of observing teacher activities and student learning activities. The product was also considered to fulfill the effective criteria. Based on the results of the analysis, the contextual textbook for Class VI on social science of Primary School was eligible and could be used in the learning process because it had reached the valid, attractive, practical and effective criteria.